Impact and Identities as Revealed in Tourists’ Perceptions of the Linguistic Landscape in Tourist Destinations - Sieras, Shangrela G. (International Journal of Language and Literary Studies, 2024)
The language displayed on signage, tarps, and shop fronts helps tourists navigate the place or learn how to avail of services or facilities in a destination. The availability of tourist information in a familiar language can be crucial to tourist satisfaction because tourists rely on signage information during the tour. This study analyzed tourists’ perceptions of signage in select destinations in Northern Mindanao, Philippines. This study employed a qualitative approach and used an online survey questionnaire to gather data. The participants were local tourists who were purposively sampled for this study. Their responses were analyzed using qualitative content analysis. The findings revealed four themes: tourists’ perceptions of the usefulness of signage, preferred language in signage, perceptions of destinations that use English signage, and impressions of visitors to destinations with English signage. Signage with both texts and symbols was found useful in navigating the destination. English signage is perceived as convenient and helpful in making tourists feel secure in a new place. It is equated with the progress and sophistication of the destinations and their visitors. This study concludes that while English is perceived with high valuation as a lingua franca in tourism, the need to use multilingual signage is desired. The tourists’ linguistic preference is a challenge to LL actors to be more adaptive to tourists’ language choices while not sacrificing the authentic experience at the destination. Sign makers should consider how linguistic elements in signage shape the tourist destinations’ image and tourists’ satisfaction in general. Keywords: Linguistic landscape; English signage; qualitative content anaysis; tourists’ perceptions